Influence of the Protonation State on the Excited-State Dynamics of Ruthenium(II) Complexes with Imidazole π-Extended Dipyridophenazine Ligands - Müller, Carolin; Isakov, Dajana; Rau, Sven; Dietzek, Benjamin (Journal of Physical Chemistry A, 2021)
Ruthenium(II) complexes, like [(tbbpy)2Ru(dppz)]2+ (Ru-dppz; tbbpy = 4,4′-di-tert-butyl-2,2′-bipyridine, dppz = dipyrido-[3,2-a:2′,3′-c]phenazine), have emerged as suitable photosensitizers in photoredox catalysis. Since then, there has been ongoing interest in the design of π-extended Ru-dppz systems with red-shifted visible absorption maxima and sufficiently long-lived excited states independent of the solvent or pH value. Herein, we explore the photophysical properties of protonation isomers of the linearly π-extended [(tbbpy)2Ru(L)]2+-type complexes bearing a dppz ligand with directly fused imidazole (im) and methyl-imidazole units (mim) as L. Steady-state UV-vis absorption, resonance Raman, as well as time-resolved emission and transient absorption spectroscopy reveal that Ru-im and Ru-mim show desirable properties for the application in photocatalytic processes, i.e., strong visible absorbance and two long-lived excited states in the 3ILCT and 3MLCT manifold, at pH values between 3 and 12. However, protonation of the (methyl-)imidazole unit at pH ≤ 2 unit causes decreased excited-state lifetimes and an emission switch-off.
CRIS-Team Scopus Importer:2023-11-13